Impact of manufacturing structure upgrading on industrial land prices from the perspective of government intervention: Take Beijing-Tianjin-Hebei and Yangtze River Delta urban agglomerations as examples - LIN Ruihan, ZHU Daolin, QI Yuan (Ziyuan Kexue, 2025)
[Objective] As an essential production factor for business operation, industrial land prices play an important role in promoting the efficient use of urban industrial land and supporting regional industrial economic growth. This study aims to elucidate the variations in the impact of manufacturing structure upgrading on industrial land prices under different degrees of government intervention, thereby providing references for the market-oriented reform of industrial lands. [Methods] This study selected 98599 micro-level industrial land transaction records from 40 cities in the Beijing-Tianjin-Hebei (BTH) and Yangtze River Delta (YRD) urban agglomerations from 2007 to 2019. Using a threshold regression model, this study revealed the impact of the manufacturing structure upgrading on industrial land prices under different degrees of government intervention, considering both full-sample analysis and heterogeneity across urban agglomerations. [Results] (1) Manufacturing structure upgrading has a significantly driving effect on industrial land prices. (2) From the perspective of government intervention, the effect of manufacturing structure upgrading on land prices varied. As the level of intervention increased, its positive impact on land prices gradually weakened. (3) The impact of manufacturing structure upgrading on industrial land prices showed significant differences across urban agglomerations. In the BTH urban agglomeration, this effect was statistically insignificant. However, in the YRD urban agglomeration, it significantly boosted land prices, although this effect weakened as government intervention intensified. [Conclusion] Manufacturing structure upgrading drives up industrial land prices by increasing returns on industrial land; however, this positive relationship weakens as government intervention intensifies. In the future, the Chinese government should fully leverage market mechanisms’decisive role in industrial land allocation, improve the land valuation framework, and establish a sound and transparent pricing system.